Economic times' statistical survey of the Indian economy (New Delhi, 1984)
This book contains following topics: Population; National Income; Agriculture and Allied Sectors; Industry and Minerals; Energy; Corporate Sector; Money and Banking; Prices; Foreign Trade and Balance of Payments etc.
Keywords: Economic surveys - India